A Systematic Review of the Impact of COVID-19 on Children's Outcomes - Nurhidayah, Ikeu; Mega Tamara; Dyah Setyorini (Universitas Airlangga, 2024)
Background: The COVID-19 pandemic has had an impact on the health of children. Nurses and healthcare professionals should know the latest information regarding the impact of Covid-19 on children. Aims: This literature review aims to identify the impact of COVID-19 on children's outcomes. Method: This literature study uses the narrative review method. CINAHL, PubMed, Proquest, Science Direct, and Google Scholar were used to conduct the literature search. The keywords used are